JURASSIC MANGANESE CARBONATES OF CENTRAL-EUROPE AND THE EARLY TOARCIAN ANOXIC EVENT - Jenkyns, H; Geczy, B; Marshall, J (1991)
The intimate stratigraphical association between Lower Toarcian manganese carbonates and carbon-rich shales in Austria, Czechoslovakia, Germany, Hungary, Italy, and Switzerland is suggestive of a genetic connection between the two, given the similar anoxic to euxinic depositional environments in which both these distinctive sediments form today. Ammonite biostratigraphy and carbon-isotope stratigraphy suggest that these metalliferous deposits are everywhere of identical age, namely tenuicostatum to early falciferum Zones. Recognition of an early Toarcian anoxic event in the Alpine-Mediterranean domain, characterized by the development of a well-developed oxygen-minimum zone across the rifted proto-continental margins of the Tethys, indicates that these metalliferous deposits can be related to mid-water transport of manganese, possibly of continental derivation. -from Authors